2013
DOI: 10.1016/j.urology.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Struvite Urolithiasis and Chronic Urinary Tract Infection in a Murine Model of Urinary Diversion

Abstract: OBJECTIVES To characterize the clinical course following cutaneous vesicostomy (CV) in megabladder (mgb−/−) mice with functional urinary bladder obstruction. MATERIALS AND METHODS Forty-five mgb−/− males underwent CV at a median age of 25 days. The 34 animals that survived longer than 3 days after CV were evaluated by serial observation and renal ultrasound. Moribund animals were euthanized. Urinary bladders and kidneys were analyzed by histopathology, and urine biochemical studies were performed. RESULTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 19 publications
0
10
0
10
Order By: Relevance
“…This made us consider that all the CoNS except for the one previously described were external contaminants of the calculi. Nevertheless, there are few studies which found CoNS as real etiological agents in UTI and calculi, especially when prosthetic devices were inserted (25,26). Similar to CoNS, Chryseobacterium indologenes and Leuconostoc pseudomesenteroides were identified only after enrichment, so we also interpreted them as external contaminants.…”
Section: Discussionmentioning
confidence: 84%
“…This made us consider that all the CoNS except for the one previously described were external contaminants of the calculi. Nevertheless, there are few studies which found CoNS as real etiological agents in UTI and calculi, especially when prosthetic devices were inserted (25,26). Similar to CoNS, Chryseobacterium indologenes and Leuconostoc pseudomesenteroides were identified only after enrichment, so we also interpreted them as external contaminants.…”
Section: Discussionmentioning
confidence: 84%
“…A eliminação incompleta de urina predispõe a infecções urinárias e à formação e precipitação de cristais (TAN et al, 2013;BECKNELL et al, 2013). A atonia de bexiga, o divertículo vesical e divertículos caliceais predispõem à enfermidade devido à estase urinária (OSBORNE et al, 1995;TAN et al, 2013;BECKNELL et al, 2013).…”
Section: Alterações Congênitas Anatômicas E Funcionaisunclassified
“…A ureia é um produto do catabolismo dos aminoácidos. Quando hidrolisada pela urease produz grandes quantidades de íons de amônio e carbonato, alcalinizando a urina progressivamente, o que reduz a solubilidade de estruvita e fosfato de cálcio, favorecendo a precipitação (OSBORNE et al, 1995;ULRICH et al, 2008;BECKNELL et al, 2013). Além de ser fator de predisposição à urolitíase, a infecção bacteriana também pode ocorrer secundariamente ao problema (GATORIA et al, 2006;KOEHLER et al, 2008).…”
Section: Infecções Bacterianasunclassified
See 2 more Smart Citations